2016
DOI: 10.1177/2372732216685861
|View full text |Cite
|
Sign up to set email alerts
|

Professional Credentialing of Practicing Behavior Analysts

Abstract: The high demand for ABA services has resulted in the rapid growth in the number of credentialed practitioners around the world in recent years. Key Points • • Applied behavior analysis has been demonstrated as a highly successful treatment approach in a variety of areas, including autism, substance abuse treatment, gerontology, brain injury rehabilitation, and occupational safety, among others. • • In less than two decades, the BACB has credentialed more than 50,000 behavior analysts and behavior technicians i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…In a recent systematic review on the U.S. healthcare workforce for children with ASD, investigators concluded that there is limited geographic availability of specialty providers and that there is a need for research that further explores the accessibility of this workforce (McBain et al 2019 ). Largely in response to increased demand for ABA services for children with ASD (Carr & Nosik 2017 ), the number of BCBAs in the U.S. has risen dramatically. In 1999, there were 28; by January 2019, twenty years later, the number of active BCBAs totaled 27,289 (Behavior Analyst Certification Board 2019a ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review on the U.S. healthcare workforce for children with ASD, investigators concluded that there is limited geographic availability of specialty providers and that there is a need for research that further explores the accessibility of this workforce (McBain et al 2019 ). Largely in response to increased demand for ABA services for children with ASD (Carr & Nosik 2017 ), the number of BCBAs in the U.S. has risen dramatically. In 1999, there were 28; by January 2019, twenty years later, the number of active BCBAs totaled 27,289 (Behavior Analyst Certification Board 2019a ).…”
Section: Introductionmentioning
confidence: 99%
“…2 Carr et al ( 2017 ) reported that the RBT® credential was created “in response to various stakeholders (e.g., funders, legislators) who sought a credential for the individuals who actually make direct contact with clients” (p. 164). Specifically, an individual with an RBT® certification is a person who: (a) is at least 18 years old, (b) has a high school diploma or national equivalent, (c) passes a criminal background check, (d) completes a 40 h training based upon the task list the BACB® has created, (e) passes a direct observation competency assessment, (f) passes a written exam, and (g) pays all fees (Carr and Nosik 2017 ). Additionally, RBTs® are required to practice under the supervision of a BCBA®.…”
mentioning
confidence: 99%
“…(A BCBA with a doctoral degree is designated as a BCBA-D.) As of March 2018, the BACB has credentialed 28,037 BCBAs, 2,958 BCaBAs, and 37,127 RBTs for a total of 68,122 individuals (BACB, n.d.-a) in more than 70 countries. The number of certificants from 1999 to the present shows a consistent increasing trend (Carr & Nosik, 2017). Certification through the BACB has become the primary criterion for defining what it means to be a practitioner of ABA.…”
Section: Developments In Behavior Analysismentioning
confidence: 99%